Ходит дом ходуном - Яковлев Лев Григорьевич (Веселые истории веселых писателей, 1998)
Экземпляры: аб. (2000) / Инвентарный номер: 41855 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Я 47 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5